Phytochemical screening and DPPH radical scavenging activity of three morphotypes of Mauritia flexuosa L.f. from Peru, and thermal stability of a milk-based beverage enriched with carotenoids from these fruits - Best, Ivan (2020)
Mauritia flexuosa L.f. is a palm tree which presents great morphological variability (morphotypes), represented mainly by the mesocarp color of its fruits. The objective of the study was to characterize the physicochemical and antioxidant properties of three morphotypes of Mauritia flexuosa L.f. (Yellow, Colour and Shambo) of greater economic importance in the Peruvian Amazon. Shambo showed a significantly high content of bioactive compounds (total phenolics, flavonoids and carotenoids) and DPPH radical scavenging activity compared to the Yellow and Colour morphotypes (p <= 0.05). There was a significant correlation between DPPH radical scavenging activity and total phenolics, flavonoids and carotenoids (p <= 0.01). Furthermore, milk-based beverages enriched with carotenoids of those morphotypes of Mauritia flexuosa L.f. have been shown to be a good source of bioactive compounds for use in the food industry. The milk-based beverages enriched with carotenoids of those morphotypes of Mauritia flexuosa L.f. showed higher lightness (L*) and yellowness (b*).